2022
DOI: 10.1111/jofi.13107
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Policy and Asset Valuation

Abstract: We document large, longer-term, joint regime shifts in asset valuations and the real federal funds rate-r* spread. To interpret these findings, we estimate a novel macro-finance model of monetary transmission and find that the documented regimes coincide with shifts in the parameters of a policy rule, with long-term consequences for the real interest rate. Estimates imply that two-thirds of the decline in the real interest rate since the early 1980s is attributable to regime changes in monetary policy. The mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(21 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Similar to Bianchi et al. (2022), we also display the monetary policy spread (right‐hand side), defined by the authors as the difference between the real and natural interest rate indicating the monetary policy stance. However, in our case, the real interest rate measure captures only the contributions of the inflation target shock, and consequently, the policy stance displayed on the right‐hand side of Figure 3 accounts only for the inflation target instrument.…”
Section: Resultsmentioning
confidence: 84%
“…Similar to Bianchi et al. (2022), we also display the monetary policy spread (right‐hand side), defined by the authors as the difference between the real and natural interest rate indicating the monetary policy stance. However, in our case, the real interest rate measure captures only the contributions of the inflation target shock, and consequently, the policy stance displayed on the right‐hand side of Figure 3 accounts only for the inflation target instrument.…”
Section: Resultsmentioning
confidence: 84%
“…Specifically, the output coefficient decreases (increases) towards the end (beginning) of a tightening cycle and monetary easings tend to be implemented quickly, while tightenings occur more gradually. Bianchi et al . (2022) documented large shifts in the parameters of the US monetary policy rule over the past few decades and concluded that infrequent changes in the monetary stance can lead to persistent shifts in the real interest rate and asset valuations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The bifurcation from a stable price regime when 2αγ * > ψ 2 to the explosive regime when 2αγ * ≤ ψ 2 , just from a change of expectation of the reference price and/or earnings, provides a simple formal rationalisation of the common lore that financial markets are characterised by shifts between stable and unsustainable exuberant regimes. For instance, Bianci et al [2022] shows that the US economy can be characterised by longer-term regime shifts in asset values that synchronise with shifts in interest rates.…”
Section: Classification Of Two Different Regimesmentioning
confidence: 99%